The role of educational supervisors in supporting the implementation of the Deep Learning Curriculum and the Love-Based Curriculum (KBC) at Madrasah Tsanawiyah in Tarakan City - M.Ja’far Shodiq (Journal of Education and Teaching Learning, 2026)
This study aims to analyze the role of educational supervisors in supporting the implementation of the Deep Learning Curriculum and the Love-Based Curriculum (KBC) at Madrasah Tsanawiyah (Islamic junior high schools) in Tarakan City. The study used a qualitative approach through observation, in-depth interviews, and documentation studies involving madrasah supervisors, madrasah principals, teachers, and educational stakeholders.The results indicate that madrasah supervisors play a strategic role as academic supervisors, facilitators, and change agents in overseeing the implementation of the Deep Learning Curriculum and the Love-Based Curriculum through academic supervision, teacher professional development, assistance in developing curriculum-aligned learning materials, and strengthening a learning culture that fosters critical thinking, collaboration, communication, and character development based on the value of love.However, implementation still faces obstacles such as a limited number of supervisors, high workloads, varying teacher competencies, and limited resources. Therefore, strengthening supervisor competencies, collaborative supervision, utilizing digital technology, and synergy among stakeholders is necessary. This study confirms that optimizing the supervisor's role is key to the successful implementation of the Deep Learning Curriculum and the Love-Based Curriculum in madrasahs.